EFFECT OF AVOCADO (Persea americana Mill var. Hass) RESIDUES SUPPLEMENTATION ON RABBIT HEALTH PROFILE, AND MEAT QUALITY - Evelyn Regalado-Rentería; Miriam Aracely Anaya-Loyola; Mariela Camacho-Barrón; Antonio De León-Rodríguez; Josué Israel García-López; Hebert Luis Hernández-Montiel; José Guadalupe Gómez-Soto; Gregorio Álvarez-Fuentes (Journal of Animal and Plant Sciences, 2025)
The aim of this study was to evaluate changes in body weight and serum metabolic parameters in meat-producing New Zealand rabbits fed a diet supplemented with 2% Hass avocado peels (P) and seeds (S). The evaluated variables included meat color, pH, moisture content, water-holding capacity, fatty acid profile, malondialdehyde levels as an oxidation parameter, measured by the TBARS (thiobarbituric acid reactive substances) test. It was found that serum concentrations of glucose, total cholesterol, triglycerides and transaminases remained unchanged throughout the experiment across treatments P and S, as well as in comparison to the control treatment (C) (p<0.05). Supplementation with P and S did not affect the normal growth curve of the rabbits, as it was similar to that of C. There were no differences in final weight among the three treatments, nor in carcass quality. At the end of the experimental period, the meat the characteristics of rabbits supplemented with P and S were similar (p>0.05) to those of the C treatment for all the evaluated response variables. Thus, the addition of 2% avocado peels and seeds to the regular diet of rabbits, had not adverse effects on their normal growth and metabolism, nor did it significantly influence meat quality characteristics or oxidative stability.
Keywords: avocado waste; New Zealand rabbits; oxidation in meat